Havre ou enfer: les caractéristiques des bars dans L’homme qui penche de Bertrand de Robillard - Mootosamy, Vidoolah (Ponti/Ponts, 2021)
The starting point of this article is an analysis of the novel L’homme qui penche of the mauritian writer Bertrand de Robillard. To start I review the ambiguous and paradoxical relationship of the main character with drinking establishments. I investigate on the function of bars as places of perdition and socialising. Some similarities will be analysed between this novel and La Modification by Michel Butor. The main character is a writer, who goes through a creative crisis. The writer spends his time wandering mechanically from one bar to another. My analysis sheds further light on the process of change the main character goes through. His transformation happens on three different levels: physical, mnemonic and introspective.